Global Issues in Early Childhood Education at Universitas Pendidikan Indonesia Bandung Toward World Class Education - M. Thontawi; Kasful Anwar Us; Fridiyanto , Fridiyanto; Sri Kadarsih (Tinta Emas Institute, 2025)
This study explores the strategies and readiness of the Early Childhood Education (PAUD) Program at Universitas Pendidikan Indonesia (UPI) in developing a global-standard education model rooted in local and national values. Using a qualitative descriptive approach, data were collected through observation, interviews with educators and administrators, and document analysis at TK-KB-DC Lab UPI Bumi Siliwangi. The findings reveal that UPI’s laboratory school implements a contextual learning ecosystem by integrating child-centered pedagogy, holistic-integrative early education, and multicultural values, while incorporating national curriculum regulations. The learning environment fosters creativity, empathy, and independent thinking through thematic, play-based, and multisensory activities. Strategies such as the BKBB (Culture, National Character, and Play) model, international partnerships, digital learning integration, and active parent involvement highlight the institution’s adaptability to global education demands. This research concludes that UPI successfully builds a prototype of early childhood education that is globally competitive yet deeply rooted in Indonesian cultural and educational values, supporting the vision of World Class Education.